Uterus-preserving management of pyomyoma: Case report of a rare complication after uterine artery embolization - Jana Busshoff; Fabinshy Thangarajah; Bernd Morgenstern (Elsevier, 2022)
Background: Pyomyoma of the uterus is a rare but severe complication of uterine artery embolization (UAE). This report describes the uterus-preserving management of a case of fast-developing pyomyoma. Screening methods to minimize the risk of this condition are discussed. Case: A 46-year-old woman presented with fever, abdominal pain and blood stream infection on the third day after UAE, which had been performed to treat symptomatic uterine myomatosus. Broad-spectrum antibiotics proved inadequate. Magnetic resonance imaging (MRI) showed a possible superinfection of the necrotic myoma. Vaginal smear showed the same organism, a resistant Escherichia coli, as in the blood culture. Because the patient declined hysterectomy, multiple hysteroscopies with removal of necrotic pyomyoma were performed. In addition, an intrauterine gentamicin chain was placed. To our knowledge, this is the first case of pyomyoma immediately after UAE and the first report of successful hysteroscopic treatment in a septic patient. Conclusion: In order to reduce the risk of pyomyoma, pre- and postinterventional algorithms should be used.